Biodegradable and highly conductive polymeric blend based on the latex of Calotropis gigantea as solid electrolyte in energy storage applications. (February 2023) - Taneja, Neha; Dujearic-Stephane, Kouao; Agrawal, Namrata; Kumar, Ashwani; Singh, Pushpa; Bharti,; Gupta, Meenal; Kumar, Yogesh
A blend polymer based on the latex of the South-Asian giant milkweed Calotropis gigantea (CGL) combined with poly (vinylidene fluoride)-co-hexafluoropropylene (PVDF-HFP) at a mass ratio of 1:1 without the addition of doping salts was synthesized via solution casting to prepare an ionic conductive film. The morphology, crystalline state, vibrational and thermal properties of the film were investigated by Scanning electron microscopy, X-ray diffraction, Fourier Transform infrared spectroscopy (FTIR), Thermal gravimetric analysis (TGA) and Differential scanning calorimetry (DSC). The ionic conductivity and transport properties were investigated by using electrochemical impedance spectroscopy (EIS) Technique. Due the highest ionic conductivity at room temperature (2.7 x 10 −2 S/cm), all-solid-state electrolyte was assembled using the prepared polymer film and a comparative study was conducted with respect to 1M H2 SO4 liquid electrolyte, regarding the specific capacitance and the electrical properties. The results demonstrate that the fabricated all-solid-state supercapacitor using PVDF-HFP/CGL blend polymer film as electrolyte matches the performance of the liquid electrolyte.